Coal miners and farmers : a social history of the Te Akatea rural farming settlement and its ‘Scots’ mining village of Glen Massey, 1900-1945 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History, Massey University, Manawatu, New Zealand - Stone, Douglas (Massey University, 2024)
This thesis examines the early 20th century development of Glen Massey within the late 19th century settlement of Te Akatea The more financially secure settlers in the isolated and topologically challenging settlement of Te Akatea, west of Ngāruawāhia were farmer entrepreneurs who viewed themselves as a leading ‘class’ by virtue of their imperial military service and the amount of land they had accrued and cleared. They not only sought to exploit the coal resources on their land, but were significant movers in the creation of commercial entities and infrastructure to do so. These efforts led to the opening of the Waipā mine and its private railway to Ngāruawāhia and the construction of the mining village of Glen Massey and an influx of mining immigrants, predominantly highly unionized Northern English in 1914. On the face of it, these immigrants represented a direct threat to the conservative social values that had hitherto obtained in Te Akatea, although in fact, miners shared the farmer ethos of ‘getting on’ by dint of hard work. The new village was effectively run by a loose cabal of company, union and church laymen. The coincidence of the start of the village and the outbreak of World War One induced issues around conscription and sedition which also incidentally flagged the ongoing issue of how media controlled the narrative of Glen Massey’s story at various stages. The construction of sport and leisure facilities and subsequent participation manifests both traditional mining, farming and gender cultures and some seminal indications of cultural shift. There were struggles for the provision of adequate housing, health and secondary education in the context of both a steadily declining mine output, shorter hours and lower wages towards the end of the 1920s. The Wilton Mine, which opened after the closure of the Waipā mine, did not really live up to employment and wage-paying expectations for the next decade. In the context of falling demand and reduced hours caused by the Depression, Glen Massey was torn by contending forces of the broader national agenda of the mining union agenda and local imperatives, particularly around home ownership. They finally opted for the latter, which entailed an enormous cost in terms of wider mining bonds. This had a complementary, if not causative disintegrating impact on the activity of the Church congregations, in particular the Methodist Church. Local economic hardship provided an opportunity for the farming community to reassert a degree of control after fifteen years of relative insularity through various, ostensibly unrelated events: a School Committee coup; discontinuance of the highly successful school Soccer team in favour of Rugby Union and a serious attempt to establish an adult Rugby Union team. Strategic withdrawal into an ‘invented past’ with Glen Massey being retroactively constructed as a ‘Scots Village’ was one avenue explored to counter the perceived threat to traditional social patterns. The breaking of the traditional ‘ties that bind’ also stimulated a search for alternative agents of social change within the community as a whole. However, there is evidence that for at least a significant segment of the farming community, local society continued to be constructed around a ‘class’ mindset which posited themselves at the apex and miners at the base.
Figures are reproduced with permission.
Keywords: 430320 New Zealand history